Public-Private Partnership in Telecommunications Infrastructure Projects : Case of the Republic of Congo - World Bank (Washington, DC, 2013)
This paper delineates the role of government in Public-Private Partnerships (PPP) in the telecommunication sector in the Republic of the Congo. PPPs offer policy makers an opportunity to improve the delivery of services and the management of facilities, and help to mobilize private capital which in turn speeds up the delivery of public infrastructure. Along with power and transportation infrastructure projects, telecommunication figures among the most growing area in PPP projects in Africa. Nevertheless, fitting telecommunication projects into a PPP model is challenging. In order to address these challenges, this paper also summarizes the achievements in Congo's economic infrastructure sector, the risks allocated to the implementation of the project, and recommends World Bank Group risk mitigation instruments.